New architecture for the UN human rights treaties monitoring mechanisms : merging and partitioning the committees - Benneh, Emmanueal Yaw (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.